Klotho in age-related cardiovascular diseases: Insights into mitochondrial dysfunction and cell death - Zohreh Zavvari Oskuye; Keyvan Mehri; Jamal Khalilpour; Samira Nemati; Leila Hosseini; Soleyman Bafadam; Naseh Abdollahzade; Reza Badalzadeh (International Journal of Cardiology: Heart & Vasculature)
Aging is a major risk factor for the development of cardiovascular diseases (CVD), leading to specific alterations in the heart and vasculature. Besides, the mechanisms and intracellular pathways of aging and the factors affecting it are still not completely clear. Age-related complications such as oxidative stress, decreased autophagy, mitochondrial dysfunction, inflammatory responses, and cardiac dysfunction are associated with relative Klotho deficiency. Klotho, an anti-aging protein, with anti-oxidative and anti-inflammatory properties, has been shown to modulate calcium regulation and autophagy. It also protects against endothelial dysfunction by increasing nitric oxide production. Furthermore, emerging research has revealed that klotho significantly impacts vascular smooth muscle cells (VSMC) energetics and survival. This article has focused on recent advances in using Klotho in age-related CVD and summarizes the pre-clinical evidence supporting this approach. Based on the research, Klotho could provide more therapeutic options for ameliorating aging-related CVD.